Diversity of communities and economic development: An overview - Gustav Ranis (Yale University, Economic Growth Center, 2011)
This paper reviews the literature on the impact of ethnic diversity on economic development. Ethnically polarized societies are less likely to agree on the provision of public goods and more likely to engage in rent seeking activities providing lower levels of social capital. Initial conditions are important determinants of adverse development outcomes. The role of decentralization, democracy and markets as potential remedies are discussed. The paper then presents a number of preliminary hypotheses on the relationship between diversity and instability in order to stimulate future research.
Keywords: O11; O40; O43; O55; 330; Africa; Diversity; Economic Growth; Instability